N 스크린 서비스 이용자의 이용 동기와 불만족 요인에 관한 연구 - 임소혜(Sohei Lim); 이영주(Young-Ju Lee) (한국콘텐츠학회 논문지, 13(3), 2013)
This research attempts to identify N-screen users' motivational and dissatisfying factors in relation to their willingness for continued future use of the service. An on-line survey was conducted (N=558) to reveal five major factors for N-screen use: Medium usability (interface usability and daily usefulness), Socialness (potential for social use with family and friends), Mobility (use without restraints of time and space), Contents (diversity of contents catalogue and related information search), and Habitual use. With exception of Contents factor, four of those factors were proven to be meaningful predictors of the users' willingness for continued future use of N-screen service. Meanwhile, two factors were extracted as the major source for N-screen users' dissatisfaction: Customer service (dissatisfaction associated with the service itself) and Contents (dissatisfaction relating to contents use). The effect of those two dissatisfaction factors was examined. The results show that Contents dissatisfaction, in comparison with Customer service dissatisfaction, was a more powerful predictor for discontinuing of N-screen service use. 본 연구는 N 스크린 이용자들 이용 동기와 불만족 요인을 조사하고 이를 앞으로의 지속적인 이용 의사와 연결시켜 분석하고자 하였다. 온라인 설문 조사(N=558) 결과, N 스크린 이용 동기는 인터페이스의 편의성과 일상생활에서의 유용성에 관한 항목인 '매체활용성', 가족/친구 등과 함께 사회적 이용에 관한 '사회성', 시간과 공간에 구속받지 않는 이용과 이동성에 관한 '휴대성', N 스크린 서비스가 제공하는 콘텐츠의 다양성과 연계 정보 검색 가능성에 관한 '콘텐츠속성', 그리고 '습관성'이라는 다섯 요인이 추출되었다. 다섯 동기 요인 중 콘텐츠 속성 동기를 제외한 나머지 네 가지 동기가 모두 이용 지속 의사에 유의한 예측력을 지니는 변인으로 식별되었다. 한편 N 스크린에 대한 불만족 요인으로는 서비스와 관련된 '고객 서비스 불만족' 요인과 콘텐츠 이용 과정에서 나타나는 다양한 불편함과 관련된 '콘텐츠 이용 불만족'으로 정리될 수 있었으며 콘텐츠 이용 불만족 요인이 고객 서비스 불만족 요인보다 약간 높게 드러났다. N 스크린의 불만족 요인이 이용 지속 의사에 미치는 영향을 살펴본 결과 고객 서비스 불만족 요인보다는 콘텐츠 이용 불만족 요인이 이용 지속 의사에 부정적 예측력을 지니는 것으로 나타났다.